The effect of annealing to the hardness of oxide dispersion strengthened (ODS) Fe-15cr-0.3y2O3 alloy - Shamsudin F.M.; Abdullah Y.; Radiman S.; Hamid N.A. (Trans Tech Publications Ltd, 2023)
Annealing; Breeding blankets; Dispersions; Grain growth; Industrial research; Iron alloys; Mechanical alloying; Metallic matrix composites; Microstructure; Nanoparticles; Pelletizing; Powders; Scanning electron microscopy; Sintering; Vickers hardness; Vickers hardness testing; X rays; Effect of annealing; Field emission scanning electron microscopes; High temperature; Micro Vickers hardness; Oxide dispersion strengthened; Powder particles; Spherical shape; Zener-pinning; Chromium alloys